Distribuição vertical das larvas de Neritina zebra (BRUGUIÈRE, 1792) (mollusca: gastropoda) durante a maré vazante da Baía do Guajará (PA) - MONTEIRO, Raqueline Cristina Pereira (2019)
In estuaries, the larvae have different vertical migration strategies to minimize or maximize their export or retention according to their embryonic and larval development. This study was carried out in the bay of Guajará and aimed to determine a pattern of vertical distribution in the water column in relation to the density and size of the larvae Neritina zebra during the ebb tide. Thus, samples of plankton were collected in December (2013) and three phases were defined during the ebb tide, initial (after high tide), peak phase (maximum ebb) and finals (near low tide); and two depths: near the surface (referred as 'surface') and mid-water (in approximate depth of 4m). The velocity of flow in the water column were obtained by a ADCP (acoustic Doppler current profile). The tide and the depth were factors that influenced the distribution and behavior of individuals. The variation of the average speed along the ebb interfered in the distribution of individuals; so were observed a decrease in the average density during the ebb tide. In addition, the average size of smaller larvae was located at the surface while the larger average size in the depth of half-water. So it was clear that all larvae showed downward migration as a mechanism to minimize the effect of export downstream.